Aberrant high expression of the TET1 gene in Hirschsprung's disease - Shaobo Yang; Jianghong Yu; Hong Yang; Wanwei Zheng; Ying Zhou; Yanlei Huang; Gong Chen; Shan Zheng (Elsevier, 2022)
Background: The pathogenesis of Hirschsprung's disease (HSCR) remains unclear but might involve genes participating in neural crest development. Gene methylation controls the expression of many genes and is involved in the development and migration of neural crest cells, but the involvement of demethylation in HSCR is unknown. This study aimed to investigate the expression of ten-eleven translocation methylcytosine dioxygenase 1 (TET1) (a demethylation protein) in patients with HSCR. Methods: This is a retrospective study of surgical specimens from paediatric patients with and without HSCR (e.g., intussusception and incarcerated hernia) obtained from 07/2015 to 08/2017. TET1 expression was determined by qRT-PCR, western blotting, and immunohistochemistry. The levels of 5-hydroxymethylcytosine were determined by the dot blot assay. Results: The specimens of 35 patients with HSCR and 25 controls were collected. The median TET1 mRNA expression values were 1.028 [HSCR-stenotic (S)], 0.908 [HSCR-dilated (D)], and 0.467 (control) (HSCR-S vs. control: P = 0.002; HSCR-D vs. control: P = 0.008; HSCR-S vs. HSCR-D: P = 0.44). TET1 protein levels followed a similar pattern. The intensity of immunostaining identified higher expression of TET1 in HSCR colon tissues compared with control tissues. The 5-hmC levels in HSCR stenotic segment samples were significantly higher than those in controls. Conclusion: The expression of TET1 is higher in paediatric patients with HSCR than in controls. DNA demethylation initiated by TET1 may be related to HSCR, which demonstrates that TET1 may play a role in the development of HSCR.